Keynes, Trouton and the Hector Whaling Company. A personal and professional relationship - Basberg, Bjørn L (Business History, 2017)
John Maynard Keynes’ activities on the stock market are well known. One company in which he bought stocks was the Hector Whaling Company Ltd., London – a comparatively small and little known company founded in 1928. The director of this company was Rupert Trouton. He had worked with Keynes for the Government during the First World War, was his student at Cambridge, and became a close partner in the City from the 1920s and onwards. The reason why Keynes invested in Hector was obviously his association with Rupert Trouton. The first part of this paper explores briefly the development of the Hector Whaling Company and its origins in Norway. The main part analyses the relationship between Trouton and Keynes. The focus is on their co-operation relating to Hector Whaling, but their relationship regarding various other businesses, as well as on the personal level, is also described. The paper is based on studies of the Keynes archives in Cambridge as well as newly available archives of the Hector company. The analysis provides new insights to the more general question on the motivations and decisions behind Keynes’ stock market investments as well as the internationalization of the whaling industry in the 1920s and 30s.
Publisher: Routledge
Keywords: Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; økonomi

Kaptein Melsom. Et spennende liv som hvalfanger og skipsreder - Dyrhaug, Tore (Njotarøy : årsskrift, 2015)
1912 fikk Nøtterøy en ny innbygger. Hvalfangeren H. G. Melsom var vendt hjem fra et hvalfangerliv i det fjerne Østen og kjøpte hus på Ørsnes. Her startet han opp en ny fase i livet, som skipsreder. Høydepunktet i hans karriere var trolig da hvalskuta «Lancing» dro om bord den første hvalen fra en opphalingsslipp i hekken på båten. Med dette var den virkelige pelagiske hvalfangsten i gang. Historien om «Lancing» som det første hvalkokeriet som kunne dra en hel hval om bord, er vel kjent og beskrevet. Dette var starten på den pelagiske hvalfangsten som brakte hvalfangsten inn i en ny fase. Men historien om hvalfangeren og rederen fra Nøtterøy, som var en av dem som sto bak, har ikke vært særlig kjent. Med god hjelp fra barnebarnet Henrik Melsom Henriksen, har Tore Dyrhaug skrevet ned denne historien.
Publisher: Nøtterøy historielag
Keywords: Nordmenn; Norge; Sørishavet; dagbøker; hvalfangere; hvalfangst; pelagisk

Thorbryn - en hvalbåts videverdige karriere - Basberg, Bjørn L (Norsk maritimt museum. Årbok, 2014)
Publisher: Norsk maritimt museum
Keywords: Sørishavet; historie; hvalbåter; hvalfangst; pelagisk; sjøfart; skipsfart

Svartelisting i isødet - Christensen, Stig H (LO-Aktuelt, 2014)
Hvalfangst-eventyret i Antarktis fra 1905 kostet menneskeliv og blodslit. Hvalfangernes forsøk på å organisere seg ble møtt med svartelisting, utestengelse og arrestasjoner.
Keywords: Antarktis; Sørishavet; arbeidsforhold; fagforbund; hvalfangere; hvalfangst; pelagisk; sjøfolk

A Crisis that Never Came: The decline of the Antarctic Whaling Industry in the 1950s and 1960s - Basberg, Bjørn L (The Mariner's Mirror, 2013)
Publisher: Routledge
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; pelagisk; økonomi

The first Antarctic whaling season of Admiralen (1905–1906): the diary of Alexander Lange - Adie, Susan; Basberg, Bjørn L; Lange, Alexander (Polar Record, 2009)
The first factory ship of the so-called modern era of Antarctic whaling was Admiralen, arriving together with two smaller catcher boats in the South Shetland Islands in January 1906, after a period of whaling in the Falkland Islands. The expedition leader was Alexander Lange, a Norwegian whaler with a long experience from whaling in northern Norway and Spitsbergen. He kept a diary for a considerable period and this covered several whaling voyages. The one dealing with the pioneer Antarctic season of 1905–1906 has been translated from Norwegian into English and is presented here with an introduction that places the expedition into its wider context.
Publisher: Cambridge University Press
Keywords: Nordmenn; Norge; Sørishavet; dagbøker; hvalfangere; hvalfangst; pelagisk

"En livbåt halvfull av vann er funnet". Forlis og ulykker i hvalfangsten på 1920-tallet - Børresen, Dag Ingemar (Norsk sjøfartsmuseum. Årbok, 2008)
Publisher: Norsk sjøfartsmuseum
Keywords: Sørishavet; hvalbåter; hvalfangere; hvalfangstindustri; hvalkokerier; isfangsten; pelagisk; sjøfolk

Pioneer whalers in the Ross Sea, 1923–33 - Barr, William; Watt, James P C (Polar Record, 2005)
On Christmas Eve 1923, the whaling factory ship Sir James Clark Ross, commanded by Captain Carl Anton Larsen and accompanied by five catchers, reached the front of the Ross Ice Shelf; these were the first whaling vessels to operate in the Ross Sea. They had been dispatched by the Norwegian whaling company Hvalfangeraktienselskapet Rosshavet, which had obtained a licence from the British government. For most of the 1923–24 season, Sir James Clark Ross occupied an uneasy anchorage in the deep waters of Discovery Inlet, a narrow embayment in the front of the Ross Ice Shelf, while her catchers pursued whales widely in the Ross Sea. During that first season they killed and processed 221 whales (211 blue whales and 10 fin whales), which yielded 17,300 barrels of oil. During the next decade, with the exception of the 1931–32 season, Sir James Clark Ross and two other factory ships operated by Rosshavet, C.A. Larsen and Sir James Clark Ross II, operated in the Ross Sea. From the 1926–27 season onwards these ships were joined by up to three other factory ships and their catchers, operated by other companies. During the decade 1923–33 the Rosshavet ships killed and processed 9122 whales in the Ross Sea sector, mainly in the open waters of the Ross Sea south of the pack-ice belt. Total harvest for all factory ships from the Ross Sea sector for the period was 18,238 whales (mainly blue whales) producing 1,490,948 barrels of oil. From 1924 onwards the Rosshavet catchers wintered in Paterson Inlet on Stewart Island, New Zealand, and from 1925 onwards a well-equipped shipyard, Kaipipi Shipyard, operated on Price Peninsula in Paterson Inlet to service the Rosshavet ships.
Publisher: Cambridge University Press
Keywords: Carl Anton Larsen; Rosshavet; Sørishavet; hvalfangere; hvalfangstselskaper; pelagisk

In the wake of Tønnessen and Johnsen : trends in whaling history research after 1970 - Basberg, Bjørn L (Discussion paper Norges handelshøyskole, Institutt for samfunnsøkonomi, 2003)
Publisher: Norwegian School of Economics and Business Administration. Department of Economics Place: Bergen
Keywords: Antarktis; Norge; husholdning; hvalfangere; hvalfangst; pelagisk; økonomisk historie

Helse på hvalfangst - Thoresen, Per (Vestfoldminne, 2002)
Publisher: Vestfoldmuseene
Keywords: Antarktis; arbeidsforhold; erindringer; helse; hvalfangere; hvalfangst; lege; medisin; pelagisk; sjøfolk; sjømenn

Productivity in the 20th century Antarctic pelagic shore station whaling: growth and stagnation in two technological regimes. - Basberg, Bjørn L (The Great Circle, 1997)
Publisher: Australian Association for Maritime History
Keywords: Antarktis; Sørishavet; historie; hvalfangstindustri; hvalfangststasjoner; hvalindustri; pelagisk

Hvalen – ressurs og politikk – Historisk overblikk - Fløistad, Brit (Vestfoldminne, 1995)
Publisher: Museumsforlaget
Keywords: Sørishavet; historie; hvalfangere; hvalfangst; pelagisk

Åpning av Foyn-seminaret 23.januar 1995 - Olsen, Jan Henry T (Vestfoldminne, 1995)
Publisher: Vestfoldmuseene
Keywords: Den internasjonale hvalfangstkommisjonen; Norge; Svend Foyn; Sørishavet; historie; hvalfangere; hvalfangst; hvalfangstkvotene; pelagisk

Hvalfangstlæge for 40 år siden - Husby, Jakob; Kolltveit, Bård (Norsk sjøfartsmuseum. Årsberetning, 1993)
Publisher: Museet Place: Oslo
Keywords: Anglo Norse ekspedisjonene; Sørishavet; erindringer; historie; hvalfangst; hvalkokerier; pelagisk

Vel blåst! Kommandør Chr. Christensens Hvalfangstmuseum gjennom 75 år 1917-1992 - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1992)
Publisher: Sandefjordmuseene Place: Sandefjord
Keywords: Antarktis; Christen Christensen; Nordmenn; Vestfold; historie; hvalfangere; hvalfangstindustri; pelagisk; polarekspedisjoner

Ingeniør Sæbjørnsens bukspretter - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Publisher: Museene Place: Sandefjord
Keywords: Nordmenn; Sørishavet; hvalfangst; hvalfangstindustri; hvalindustri; patenter; pelagisk; utstyr

Næringer i hvalfangstens grenseland - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Publisher: Museene Place: Sandefjord
Keywords: Christen Christensen; Sørishavet; historie; hvalfangst; hvalkokerier; hvalolje; næring; patenter; pelagisk; økonomi

Zwischen Kooperation und Konfrontation. Deutschland, Norwegen und die Walfangfrage in den 1930er Jahren - Scholl, Lars Ulrich (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1990)
Publisher: Stiftelsen Bergens sjøfartsmuseum Place: Bergen
Keywords: Norge; Sørishavet; Tyskland; historie; hvalfangere; hvalfangstindustri; hvalolje; pelagisk; samarbeid

På hvalfangst med blyant og farvestifter - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Publisher: Museene Place: Sandefjord
Keywords: Nordmenn; Sørishavet; historie; hvalfangst; kunst; pelagisk

Pierce's kastebørse - et "Reodor Felgen" -patent med lang levetid - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Publisher: Museene Place: Sandefjord
Keywords: Sørishavet; historie; hvalfangst; hvalolje; patenter; pelagisk; utstyr

Hjelpekrysser kaprer norske hvalfangere - Nilsen, Tore L.; Thowsen, Atle (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1989)
Publisher: Stiftelsen Bergens sjøfartsmuseum Place: Bergen
Keywords: Sørishavet; andre verdenskrig; historie; hvalbåter; hvalfangstflåten; pelagisk

Rosshavets base på Stewart Island - Hoff, Stein (Norsk sjøfartsmuseum. Årsberetning, 1987)
Publisher: Museet Place: Oslo
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; historie; hvalfangere; hvalfangststasjoner; pelagisk

Motortankskipenes inntog. En komparasjon av utviklingen i dansk, norsk og svensk skipsbyggingsindustri, ca. 1912 til 1933 - Basberg, Bjørn L (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1986)
Publisher: Stiftelsen Bergens sjøfartsmuseum Place: Bergen
Keywords: Sørishavet; historie; hvalbåter; hvalfangstindustri; pelagisk; skipsbyggerier; skipsfart

Technological transformation in the Norwegian whaling industry in the interwar period - Basberg, Bjørn L (Scandinavian Economic History Review, 1985)
Inventions, innovations and technological changes in the broadest sense are often treated as an independent process and are not subjected to any detailed attempts at explanation. It is scarcely anything exceptional, for example, that Sigurd Risting, the first historian of the whaling industry in Norway, explains the development of whaling as follows: Thus there has been a large stock of finback whales along the coast of Norway for hundreds of years without their having been an object of regular profitable hunting. The reason for this has been nothing more than lack of tackle and methods capable of making hunting possible. The moment these become available, whaling as a rational business will arise by itself out of natural necessity, so to speak." Bjern L. Basberg, b. 1952, is a research fellow in economic history at the Norwegian School of Economic and Business Administration. The article is based on a thesis of 1980 titled: Innovasjons-teori, patenter og teknologisk utvikling i norsk hvalfangst ca. 1860-1968.
Publisher: Routledge
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; teknologi; økonomi

Ti nye år: Vestfold Historielag 60 år - Thoresen, Per (Vestfoldminne, 1984)
Publisher: Vestfoldmuseene
Keywords: Sørishavet; hvalfangst; kulturhistorie; pelagisk

Hvorfor gikk det så greitt? Om nedleggelsen av hvalfangstnæringen i Vestfold - Vik, Kjell (Vestfoldminne, 1984)
Publisher: Vestfoldmuseene
Keywords: Sørishavet; Vestfold; historie; hvalfangere; hvalfangstindustri; hvalindustri; næring; pelagisk; sjøfolk; økonomi

Technological change in the Norwegian whaling industry: A case-study in the use of patent-statistics as a technology indicator - Basberg, Bjørn L (Research Policy, 1982)
This paper presents an example of the use of patent statistics as a technology indicator in one industry. The first part deals with the problem of interpretation. Through examination of several other partial technology indicators, it is concluded that at least in this industry, patent statistics provide a reliable indicator, not only for the timing of inventions, but for the timing of innovations and diffusion as well. The reason is that the intervals between the stages in the innovation process are very short. This contradicts evidence from many other industries, and it is therefore emphasized that generalizations are unwarranted. The second part of this paper deals with the possible causes of technological change in Norwegian whaling. The methodology is inspired by J. Schmookler's work. Thus, the patents are correlated with other indicators of economic development in the industry. But while Schmookler's view is that the patent activity is determined by social demand and economic growth, the conclusions for the Norwegian whaling industry point in the opposite direction: the technological transformation that took place during the 1920s and early 1930s was forced upon the firms in their efforts to cut costs, which was achieved by rationalizing production and catching methods in line with a downward price trend for whale oil.
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; teknologi; økonomi

Hvalfangerne forteller. Innsammlig av hvalfangstens tradisjonsmateriale i Vestfold - Wexelsen, Einar; Devig, Thor N (Vestfoldminne, 1981)
Publisher: Vestfoldmuseene
Keywords: Sørishavet; Vestfold; erindringer; historie; hvalfangere; hvalfangst; hvalfangstnæring; pelagisk

Smia på Fevang - Thoresen, Per (Vestfoldminne, 1976)
Publisher: Vestfoldmuseene
Keywords: Nordmenn; Sørishavet; erindringer; hvalfangere; hvalfangst; pelagisk

Hvalfangstens historie - Tønnessen, Johan Nicolay; Solhaug, Trygve (Historisk tidsskrift, 1973)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; bokanmeldelser; historie; hvalfangst; pelagisk

Joh. N. Tønnessen: Den moderne hvalfangst historie. Opprinelse og utvikling. Bind 2-4. Utgitt av Norges hvalfangstforbund, Sandefjord 1967, 1969, 1970. - Solhaug, Trygve (Historisk tidsskrift, 1972)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; bokanmeldelser; historie; hvalfangst; pelagisk

"Cutty Shark" i hvalfangsten tjeneste - Berg, Knut (Årbok. Sandefjord bymuseum, 1969)
Publisher: Sandefjord bymuseum Place: Sandefjord
Keywords: Sørishavet; historie; hvalbåter; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; skip

"Forlandet" ex "Femern" ex "Foca" - Knap, Johan (Årbok. Sandefjord bymuseum, 1969)
Publisher: Sandefjord bymuseum Place: Sandefjord
Keywords: Sørishavet; historie; hvalbåter; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; skip

Erobringen av Antarktis. Spredte glimt fra hvalfangstens historie - Brøther, Dagfinn (Teknisk ukeblad : Norges fremste på teknologi, 1968)
Keywords: Sørishavet; historie; hvalfangst; hvalfangstnæring; pelagisk

"Pelagos" ex "Athenic" - Berg, Knut (Vestfold-minne, 1964)
Publisher: Vestfoldmuseene
Keywords: Sørishavet; historie; hvalbåter; hvalfangerflåte; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk

Folketro på hvalfangst - Eriksen, Erling (Vestfold-minne, 1964)
Publisher: Vestfoldmuseene
Keywords: Sørishavet; erindringer; fortellinger; historie; hvalfangere; hvalfangst; pelagisk; sjøfolk

Noen problemer i den moderne hvalfangsts historie - Tønnessen, Johan Nicolay (Vestfold-minne, 1964)
Publisher: Vestfold historielag
Keywords: Carl Anton Larsen; Henrik Johan Bull; Svend Foyn; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; næring; pelagisk; polareksspedisjoner; økonomi

Tønsbergs sjøfart gjennom 100 år - Eriksen, Erling (Vestfoldminne, 1961)
Publisher: Vestfoldmuseene
Keywords: Sørishavet; Vestfold; historie; hvalfangstindustri; hvalkokerier; pelagisk; skipsbyggerier

Elektrisk hvaldreping - Brøther, Dagfinn (Teknisk ukeblad : Norges fremste på teknologi, 1948)
Keywords: Sørishavet; historie; hvalfangst; hvalfangstnæring; pelagisk; teknologi

Til Sydishavet på jakt efter storhvalen - Slaattelid, Aasm. (Hvalfangstliv : spesialorgan for hvalfangst, 1939)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Sørishavet; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; sjøfolk

Hvalfangsten: et tilbakeblikk og en oversikt på grunnlag av norske patenter - Swensen, T (Teknisk ukeblad : Norges fremste på teknologi, 1938)
Keywords: Sørishavet; hvalfangst; patenter; pelagisk; teknologi

Ekspansjonen i hvalfangsten. Hvaloljeprisen. - Istre, Henry R (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Antarktis; Lars Christensen; Sørishavet; hvalfangere; hvalfangstindustri; hvalindustri; hvalolje; pelagisk

Hjemkomsten. Hvlafangsten historie fra dens første begynnelse - Istre, Henry R (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Sørishavet; historie; hvalfangere; hvalfangst; pelagisk

Blåhvalungen legger på sig 100 kg. i døgnet - Ruud, Johan T (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Sørishavet; blåhval; hvalfangst; paleontologi; pelagisk; zoologi

En arbeidsnatt ombord i et hvalkokeri - Slaattelid, Aasm. (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Sørishavet; hvalfangere; hvalfangst; pelagisk; sjøfolk

Elektrisk hvalskytning - Weber, Albert (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Sørishavet; hvalfangst; pelagisk; teknologi

Omkring hvalfangsten - Bogen, Hans (Samtiden: tidsskrift for politikk, litteratur og samfunnsspørsmål, 1936)
Publisher: Aschehoug
Keywords: Sørishavet; hvalfangst; hvalfangstnæring; hvalolje; pelagisk; økonomi

Norwegians in the Antarctic - Aagaard, Bjarne (The American-Scandinavian Review, 1934)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Walfang und Forschung in der Antarktis - Steinert, Hermann (Geographische Zeitschrift, 1933)
Keywords: Antarktis; Nordmenn; Norge; Norvegia ekspedisjonene; forskning; hvalfangst; pelagisk

Antarctic Research by the Norvegia Expeditions and Others - Holtedahl, Olaf (The Geographical Journal, 1931)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Lars Christensen; Norvegia ekspedisjonene; Odd I.; Sørishavet; ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Antarctic whaling and exploration - Aagaard, Bjarne (Scottish Geographical Magazine, 1929)
Publisher: Routledge
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Whaling and Exploring in the Antarctic - Aagaard, Bjarne (Norwegian Trade Review, 1929)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Modern Norwegian Whaling in the Antarctic - Isachsen, Gunnar (Geographical Review, 1929)
Publisher: [American Geographical Society, Wiley]
Keywords: Sørishavet; ekspedisjoner; forskning; historie; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk

Den moderne hvalfangstens kausalproblemer - Johnsen, Arne Odd (Historisk tidsskrift)
Publisher: Den norske historiske forening Place: Oslo
Keywords: Sørishavet; historie; hvalfangstindustri; hvalindustri; næring; pelagisk; økonomi